Kajian Teoritis terkait Kebijakan Pembiayaan Pendidikan pada Sekolah Dasar dan Menengah di Indonesia - Muhammad Polem; Afrilia Dwi Cahya (Lembaga Einstein College (LEC), 2024)
Education financing is an issue that is still hot to discuss, because it cannot be denied that there are many problems in the field related to education financing, such as the high cost of education making many Indonesians drop out of school, not to mention being colored by various bad behavior of school officials, such as principals who deliberately rape (corruption) of education funds. This study aims to explain what elements must be understood in education financing for primary and secondary education in Indonesia based on theoretical studies. The writing method uses a literature study with a qualitative approach. Data collection techniques include reading literature from books or articles relevant to the research. Data analysis techniques using inventory, categorization, and analysis of research data. The results of the study explain that in the preparation of education financing, all school parties must first be able to understand well and thoroughly the definition of education financing itself, the legal basis, the types of education financing, the sources of education financing, and the preparation of the Draft Budget for School / Madrasah Expenditure Opinions (RAPBS / M). So it can be concluded that in implementing the formulation of education financing, the principal should cooperate with the vice principal, school treasurer, teachers, administrative staff (TU), School Committee, and several related parties, so that education financing can run effectively and efficiently.